Enhancing remote healthcare delivery in Pakistan: Integration of telemedicine with AI and wearable technologies. - Muhammad Muneeb Murtaza; Aqib Mukhtar; Ghaffar, Muhammad Talha (Journal of the Pakistan Medical Association, 2026)
Dear Editor, The healthcare system in Pakistan, particularly in the rural areas, continues to face significant challenges that adversely affect the well-being of the population. Despite some profress, significant development remain necessary. There is a shortage of health professionals, infrastructure, and essential medical resources. Several districts alack of basic health units compelling patients to travel long distances for routine check-ups. In addition to the factors mentioned above, one doctor in underdeveloped regions is often responsible for approximately 1,100 patients, which severely compromises the quality of care. Furthermore, there is also a burden on the rural populations in the form of high expenses and ineffective care due to a lack of proper machinery, especially during medical emergencies. (1) Bridging these gaps requires the integration of telemedicine with artificial intelligence (AI) and wearable technologies, which together present a promising solution. Telemedicine, by allowing remote consultations, diagnosis, and treatment, can effectively bridge the gap that hinders the medical requirements of the rural population. The potential application of AI in medicine is revolutionary, and it includes earlier diagnosis and screening through advanced image analysis, along with predictive capabilities to provide the required support in clinical decision-making (2). The introduction of wearable technologies can further enhance the medical experience by allowing Continuous vital and other health data monitoring, resulting in earlier intervention. The real benefit can be achieved by combining these technologies, where AI can analyse the data received by the wearable technologies, providing us with real insights for each person's personalized Health management. The use of these technologies also allows patients to better monitor their health, leading to better health literacy and self-management (3). Nevertheless, challenges remain in implementing these solutions in Pakistan. Inadequate internet access remains a major obstacle. Digital illiteracy also complicates the effective utilisation of these technologies, especially in the rural regions of Pakistan. Fostering awareness among healthcare professionals is also crucial. A multi-staged approach is mandatory to effectively integrate telemedicine in Pakistan. Affordable internet connectivity is also a prerequisite. The development of a regulatory body for ensuring data privacy, security, and ethical guidelines is crucial (4). In parallel, digital literacy campaigns for both healthcare workers and the general population are necessary. Incentivizing healthcare professionals to serve in rural areas and adopt telemedicine practices can help bridge the workforce gap (5). In conclusion, integration of telemedicine with AI and wearable technologies offers in precedented opportunity to revolutionise remote healthcare delivery in Pakistan. This system will help us to address the geographical barriers and significantly improve healthcare access to the entire population in real time. Realising this potential will require coordinated efforts by policymakers, healthcare professionals, and the public. Thanks,